Case report: Atypical spindle cell/pleomorphic lipomatous tumor masquerading as a myxoid liposarcoma or intramuscular myxoma - Ichikawa, Jiro; Kawasaki, Tomonori; Imada, Hiroki; Kanno, Satoshi; Taniguchi, Naofumi; Ashizawa, Tomoyuki; Haro, Hirotaka (Frontiers in Oncology, 2022)
Atypical spindle cell/pleomorphic lipomatous tumors (ASPLTs) were recently categorized as benign lipomatous tumors. However, accurate and complete preoperative diagnosis of ASPLTs may be difficult. Furthermore, diagnosis based on magnetic resonance imaging (MRI) findings is uncertain because of the varying ratios of the fat component within the tumor. Here, we report a case of ASPLT masquerading as a myxoid tumor. Although MRI findings were consistent with a myxoid liposarcoma, needle biopsy findings suggested a myxoma, and we performed marginal resection. Histopathological findings revealed infiltrating spindle cells with atypia. In addition, immunohistochemistry (IHC) showed positive staining for CD34 and heterogeneous retinoblastoma deficiency, and fluorescence in situ hybridization (FISH) showed no amplification of mouse double minute 2 homolog and no rearrangement of FUS or EWSR1. When MRI and histopathological findings suggest a myxoid tumor, IHC and FISH should be considered and performed for a precise and accurate diagnosis.